Nutrition through the lifespan - Vallis, Adrian; Video Education Australasia (Australia : Video Education Australasia, 1998)
This program look at the requirements for development during infancy, pregnancy and prenatal development, childhood, adulthood and adolescence
vol.1. Infancy (24 min.)-- vol.2. Pregnancy and prenatal development (16 min.)-- vol.3. Childhood (20 min.)-- vol.4. Adulthood (27 min.)-- vol.5. Adolescence (23 min.)
Title from title screen
Executive producer, Neil Barrett ; camera and sound, Sasha Trikojus, Ian MacMillan ; editors/graphics, Adrian Vallis
Voice over: Jenny Tudor
Keywords: Nutrition; Adolescence -- Nutrition; Adulthood -- Nutrition; Children -- Nutrition; Infants -- Nutrition; Pregnant women -- Nutrition